Study the factors affecting the cost of homestays in Kundasang, Sabah during Malaysia government movement control order (MCO) - Syarifah Hanum Ali; Tshin Lip Vui; Kamiliah @ Kamaliah Sulimat (Faculty of Business, Economics and Accountancy, 2021)
The tourism sector is one of the sectors most affected by the pandemic COVID-19. The status of the homestay programme will be maintained for the duration of the Movement Control Order (MCO), as announced by the Prime Minister of Malaysia, from 18 March 2020 to an unspecified date. According to the study, tourism is one of the worst-affected industries in Kundasang, Sabah. This study aims to identify the problems inherent in the Kundasang homestay, whether the problem is internally and externally. Next, the study was to collect the recommendations for improvement to the problems faced by the community.